AS RELAÇÕES ENTRE AS VIVÊNCIAS ESPACIAIS DE ALUNAS E ALUNOS DAS INSTITUIÇÕES PÚBLICAS DE ENSINO MÉDIO REGULAR E A REPROVAÇÃO GENERIFICADA NA CIDADE DE PONTA GROSSA, PARANÁ - Oliveira, Susana Aparecida Fagundes de (2017)
This dissertation analyses the relationship between the experiences of high school public institutions‟ students and the gender failure in Ponta Grossa city, Paraná. To answer the central question of this dissertation, we stablish the following specific questions: What are the characteristics of the gender failure in high school public institutions in Ponta Grossa city, Paraná? How do the students assess their high school public institutions in Ponta Grossa city, Paraná? How is the spatiality experienced by high school students in public education institutions in Ponta Grossa city, Paraná? Therefore to produce the comprehensibility of this phenomenon, 1535 semi-structured questionnaires were applied to high school learners, with ages between 15 and 29 years, from ten public education institutions in Ponta Grossa city, Paraná. The data‟s systematization shows that 29% of the boys declare having failed during high school, whereas 17% of the girls affirmed the same. When comparing the failure percentages of boys and girls between the schools with more and with less failure, the difference between these schools was little expressive, which had an average variation of 1%. Nevertheless, the data that raises awareness the most are related to the discrepancy in the failure between boys and girls, whose average variation was 12% more among boys. These data shows that a gender failure exists.in relation to spatial experience, data shows that home and school spatiality are the most experienced places by girls, while the boys experience more spatiality in the street and at work. In this regard, it gets clear that boys and girls don‟t experience spatiality in the same manner, confirming the hegemonic rules that govern the behavioral patterns of boys and girls and this fact entails the failure behavior in the comparison between both. Not only in high schools with higher failure rates but in the schools with lower failure rates, girls tend to experience more the spatiality of home and school more than boys, this percentage being 69% girls and 65% boys relating to home, and 21% for girls and 14% for boys relating to school. In regard of the boys, these experience more the spatiality of work and street than the girls, the percentages being 8% of girls and 13% of boys relating to work, and 1% girls and 6% boys relating to the street. These data are related to the intensity of reading and the practice of sports. The boys affirm to practice 3 times more sports than the girls. On the other hand, the girls develop reading activities 3 times more than the boys. Those practices contrasting with each other, the levels of demand are completely distinct. The practice of sports demands more physical effort, while reading is more related to a mind effort. The school space has been for young students a space of conflict between being a young person and a student, since a space focused on disciplining the subject tends to homogenize young students, discarding all the possibility of an existential multitude between boys and girls, forgetting spatial experience, that are also gender related. Being so, one understands that the spaces experienced by students [home, work and street] and, especially the school space, are spaces imposed by the hegemonic power relations which are stablished through power mechanisms, in this case the gender, the adequate spaces for boys and girls, relating to a gender behavior of failure that occurs through pedagogic practice, enabled by school space.